Determination of plant growth promoting potential of enterobacteria isolated from the rhizosphere of maize (Zea mays L.) - León Mendoza, Luis H. (2014)
The yellow maize is the third most important crop in Peru and part of the chain maize-poultry-pig, significant impact on the national economic and social activity, however, in 2011, only 40% of the corn offered corresponded to the domestic industry. Looking for alternatives to reduce the use of chemical fertilizers, have performed investigations with plant growth promoting rhizobacteria. Bacteria were isolated from the rhizosphere of maize from districts Monsefú and Reque, Lambayeque. Dilution was made into sterile saline 0.87% NaCl w/v and plated on MacConkey agar, incubating at 30°C for 48 hours. 269 pure cultures of bacteria were obtained, the biochemical reaction was investigated in agar Triple sugar iron agar Iron Lysine, agar Citrate Simons, peptone broth, red broth methyl Voges-Proskauer and nitrate broth, was identified 66% as Enterobacteriaceae of genera Pantoea (49%), Klebsiella (17%), Kluyvera (16%), Serratia (11%), Citrobacter (4%) and Hafnia (3%). The native enterobacteria were quantified to 31.67 ppm of fixed nitrogen as ammonia; 54.25 ppm indole acetic acid and 4,78 ppm solubilized phosphorus, activity proteolytic and chitinolytic and antagonistic activity of Fusarium verticillioides were also determined. 16% of native enterobacteria did not affect the emergence of hard yellow maize, 77% affected positively and 7% affected negatively. In turn, none bacteria affected survival. Was demonstrated the potential plant growth promoter of enterobacteria isolated from field crops in the region of Lambayeque.